TUBERCULUM SELLAE MENINGIOMA Vs. MACROADENOMA: How to differentiate preoperatively? - Mardjono,, I.; Arifin, M. Z.; Sidabutar, R.; Singh, and, A.; Sevline, E. O. (BALI MEDICAL JOURNAL; Volume 2 Number 1, January-April 2013, 2013)
Objective: Sellar region tumors may origin from a various number of structures and each of them have a specific clinical and radiological appearance. Among these pathological processes, one of the most challenging is to distinguish between tuberculum sellae meningioma (TSM) and macroadenoma hypophysis (MH). Differentiating these two entities preoperatively is very important to decide which approach will be most suitable and beneficial. The purpose of this study is to produce a simple preoperative scoring system to differentiate these two that can be applied in specific conditions where MRI is not available or could not be performed. Methods: This analytical retrospective cohort study contains data obtained from patients treated in Neurosurgery Department of Dr. Hasan Sadikin General Hospital-Bandung from 1 January 2008 until 31 December 2010. There were 34 patients enrolled in this study, in which 15 of them were diagnosed with MH and 19 patients diagnosed with TSM confirmed with pathology examination. Results: From clinical presentation we found that the event of endocrinopathy occurs significantly in macroadenoma hypophysis (p=0.002). Whereas from radiological evaluation there were 7 parameters that significantly distinguish these two entities including hyperostosis, sellar floor configuration, homogeneity of mass, contrast agent enhancement, waist configuration, peritumoral edema, and dural attachment. From these findings, we propose a simple scoring system to differentiate macroadenoma hypophysis and tuberculum sellae meningioma with a 84.2% sensitivity and 100% specificity. Conclusion: although MRI is the modality of choice in differentiating macroadenoma hypophysis and tuberculum sellae meningioma but our scoring system can be used as an aid in choosing best surgical approach.
Keywords: sellae, region tumour, macroadenoma hypophysis, tuberculum sellae meningioma